Chiral Eutectic Mixtures and Deep Eutectic Solvents for Induced Circularly Polarized Luminescence. Issue 12 (27th September 2021) - Nelson, Brian; VandenElzen, Liam; Whitacre, Grace; Hopkins, Todd A.
Abstract: Deep eutectic solvents (DES) or eutectic mixtures prepared with a chiral component can lead to new chiral solvents with applications that include asymmetric synthesis and chiral light emitting materials. DES have low melting points, because of strong interactions, such as hydrogen bonding, between components of the mixture. Mixtures are prepared with ammonium salts, tetrabutylammonium chloride ([TBA]Cl) and choline chloride ([Ch]Cl), as hydrogen bond acceptor (HBA) and L‐lactic acid, L‐leucic acid, L‐ascorbic acid, R/S‐acetoxypropionic acid, and methyl‐(S)‐lactate as chiral hydrogen bond donors (HBD). Eight combinations of the HBAs and HBDs were prepared, and a racemic mixture of dissymmetric chiral europium complexes was dissolved in the mixtures. The circularly polarized luminescence (CPL) spectra were measured to determine the chiral discrimination by these chiral solvents. The CPL spectra show that the handedness of the chiral HBD is important to the chiral discrimination exhibited. However, the inversion of the sign of the CPL spectra in 1 : 3 [TBA]Cl:L‐lactic acid vs. 1 : 3 [Ch]Cl:L‐lactic acid, and 1 : 1.5 [Ch]Cl:L‐leucic acid vs. 1 : 1 [TBA]Cl:L‐leucic acid shows that the achiral HBA also plays a critical role in the handedness of the chiral discrimination by the chiral solvent. Abstract : Chiral solvents, including chiral deep eutectic solvents, are created by mixing ammonium salts with chiral organic molecules. A racemic europium complex is dissolved in the chiral solvent, and the circularly polarized luminescence (CPL) spectrum is measured. Results show that the achiral component is just as important as the chiral component of the solvent in the measured sign and intensity of the CPL spectrum.